Magnetic Resonance Imaging of Neuroendocrine Tumor Hepatic Metastases: Does Hepatobiliary Phase Imaging Improve Lesion Conspicuity and Interobserver Agreement of Lesion Measurements?. Issue 9 (October 2017) - Morse, Brian; Jeong, Daniel; Thomas, Kerry; Diallo, Dalanda; Strosberg, Jonathan R.
Abstract : Objective: The aim of this study was to determine if magnetic resonance imaging (MRI) performed with hepatobiliary phase imaging results in higher lesion conspicuity and produces lesion measurements with higher interobserver agreement than other MRI sequences when imaging neuroendocrine hepatic metastases. Methods: Patients who had MRIs with both gadoxetate disodium and gadopentetate dimeglumine contrast within a 6-month span were identified, and 23 hepatic lesions were selected. Three radiologists and 1 oncologist measured the greatest diameter of each lesion on the following sequences: T2 weighted, T1 weighted, postcontrast (dynamic, delayed, and hepatobiliary phase), and diffusion weighted. Signal intensity ratio (SIlesion/SIliver) and contrast-to-noise ratio ([SIlesion – SIliver]/noise) were calculated for all lesions on each sequence. The interobserver agreement of measurements on each sequence was calculated using concordance correlation coefficient. Results: Diffusion-weighted sequences had the highest signal intensity ratio ranging from 147% to 187% (vs other sequences range of 19.6%–130%). One hepatobiliary sequence had the highest contrast-to-noise ratio with a value of 41 (vs other sequences range of 3.2–28.1). Lesion measurements on all sequences showed high-interobserver agreement, with hepatobiliary sequences showing some of the highest levels of agreement. Conclusions: Our results support the use of contrast agents with hepatobiliary excretion when imaging neuroendocrine tumors metastatic to liver.